2012
DOI: 10.3928/01477447-20120621-26
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Vertebroplasty for Symptomatic Osteoporotic Vertebral Compression Fracture Adjacent to Lumbar Instrumented Circumferential Fusion

Abstract: The purpose of this study was to evaluate the efficacy and safety of percutaneous vertebroplasty for patients with symptomatic osteoporotic vertebral compression fractures adjacent to lumbar instrumented circumferential fusion. Between January 2005 and June 2010, eighteen patients in the authors' institution with lumbar instrumented circumferential fusion had adjacent symptomatic osteoporotic vertebral compression fractures. The patients received percutaneous vertebroplasty using polymethylmethacrylate bone ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…The impact of lumbar instrumented intervertebral fusion on the development of adjacent VCFs has been discussed in some studies, with evidence of an increased risk after spinal arthrodesis. 4,5,[19][20][21][22] Yang et al reported new VCFs in 150 of 1348 patients (11.1%) after posterior lumbar interbody fusion, with 108 of these (72%) being at adjacent segments. 19 Although no study has examined the relationship between new VCFs at the adjacent segment and bone loss after spinal instrumentation surgery directly, it is known that women, the elderly, and patients with osteoporosis have a specific higher incidence of new VCFs after spinal fusion, especially within the first 12 months postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of lumbar instrumented intervertebral fusion on the development of adjacent VCFs has been discussed in some studies, with evidence of an increased risk after spinal arthrodesis. 4,5,[19][20][21][22] Yang et al reported new VCFs in 150 of 1348 patients (11.1%) after posterior lumbar interbody fusion, with 108 of these (72%) being at adjacent segments. 19 Although no study has examined the relationship between new VCFs at the adjacent segment and bone loss after spinal instrumentation surgery directly, it is known that women, the elderly, and patients with osteoporosis have a specific higher incidence of new VCFs after spinal fusion, especially within the first 12 months postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Cement augmentation has been widely used in the thoracolumbar spine to treat osteoporotic compression fractures adjacent to instrumented fusion procedures. 4 More recently, it has also been reported in the cervical spine. 5 The authors report on how balloon kyphoplasty in particular can be used to simultaneously treat lytic lesions in the posterior vertebral body and also augment the stability of an anterior cage and plate construct following C7 corpectomy.…”
Section: Introductionmentioning
confidence: 90%